2022
DOI: 10.3389/fonc.2022.912639
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles From The Gut Microbiome Contribute to Tumor Immunity by Eliciting Cross-Reactive T Cells

Abstract: A growing body of evidence supports the notion that the gut microbiome plays an important role in cancer immunity. However, the underpinning mechanisms remain to be fully elucidated. One attractive hypothesis envisages that among the T cells elicited by the plethora of microbiome proteins a few exist that incidentally recognize neo-epitopes arising from cancer mutations (“molecular mimicry (MM)” hypothesis). To support MM, the human probiotic Escherichia coli Nissle was engineered with the SIINFEKL epitope (OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Five studies focused on the correlation between EVs and tumor development ( Table 2 ). Using animal models, Tomasi et al [ 122 ], Luo et al [ 92 ], and Shi et al [ 90 ] tested EVs of E. coli Nissle 1917, A. muciniphila ATCC BAA-835, and L. paracasei PC-H1, respectively. Melanoma, prostate cancer, and colorectal cancer were investigated, and comparable results were obtained despite different routes of administration and dosage; each author reported a reduction in tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies focused on the correlation between EVs and tumor development ( Table 2 ). Using animal models, Tomasi et al [ 122 ], Luo et al [ 92 ], and Shi et al [ 90 ] tested EVs of E. coli Nissle 1917, A. muciniphila ATCC BAA-835, and L. paracasei PC-H1, respectively. Melanoma, prostate cancer, and colorectal cancer were investigated, and comparable results were obtained despite different routes of administration and dosage; each author reported a reduction in tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, given the results obtained by the authors previously mentioned, it can be assumed that EVs could represent one of the effectors of these processes. For the research of Tomasi et al [ 122 ] it is necessary to highlight that they tested E. coli -EVs engineered with a cancer-specific epitope and showed that the administration of these EVs, but not of wild type EVs, induced a reduction in tumor growth ( Table 2 ). Given these results, we can assume that, unsurprisingly, not all probiotic strains may have the same health-promoting potential, although engineered EVs could represent a promising tool in cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, researchers took a shotgun sequencing of the microbiome. They sequenced the TCR of T cells and demonstrated that the main reason for tumor suppression was mediated by cross-reactive T cells triggered at the intestinal site [ 95 ]. These findings confirmed that the microbes can trigger T cell cross-reactivity through their own expression of peptides that are highly similar to tumor antigens and thus affect tumor development.…”
Section: Microbial and Tumor Neoantigensmentioning
confidence: 99%
“…Bacteria-derived EVs can affect multifarious biological processes [ 19 ]. Bacteria-derived EVs are acknowledged to be proximally or distantly related to many human diseases [ 20 – 22 ]. The role of bacteria-secreted EVs in disease treatment has attracted the attention of researchers.…”
Section: Introductionmentioning
confidence: 99%